2020
DOI: 10.1021/acsabm.9b01165
|View full text |Cite
|
Sign up to set email alerts
|

3D Diamond Electrode Array for High-Acuity Stimulation in Neural Tissue

Abstract: Innovations in micro-and nanofabrication technologies enable the manufacture of multielectrode arrays for use in neuromodulation and neural recording. Multielectrode arrays make possible medical implants such as pacemakers, deep-brain stimulators, or visual and hearing aids, to treat numerous neural disorders. An optimal neural interface requires a high density of electrodes to precisely record from and stimulate the nervous system while minimizing the overall size of the array. For example, people with retina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 47 publications
0
11
0
Order By: Relevance
“…For example, boron-doped diamond (BDD) is a p-type semiconductor, and the conductivity of BDD can be controlled by the doping level. [83][84][85] Piret et al developed 3D nanostructured BDD electrodes (Figure 5d) and used of the electrodes for recording the electrophysiology of hippocampal cells. [84] This nanostructured BDD had an impedance of 50 kΩ at 1 kHz, based on a 20 µm diameter electrode.…”
Section: Carbon-based Materialsmentioning
confidence: 99%
“…For example, boron-doped diamond (BDD) is a p-type semiconductor, and the conductivity of BDD can be controlled by the doping level. [83][84][85] Piret et al developed 3D nanostructured BDD electrodes (Figure 5d) and used of the electrodes for recording the electrophysiology of hippocampal cells. [84] This nanostructured BDD had an impedance of 50 kΩ at 1 kHz, based on a 20 µm diameter electrode.…”
Section: Carbon-based Materialsmentioning
confidence: 99%
“…Compared to the cancer research, there is less reported research that utilizes CBI devices to study neuron behavior and neurodegenerative diseases. These few studies demonstrated the capability of the CBI devices to monitor the behavior of neurons in physiological and pathogenically conditions using 2D and 3D in vitro models [84][85][86][87][88][89][90][91].…”
Section: Neurodegenerative Diseasesmentioning
confidence: 99%
“…The CBI system was also used to study the neural signals using an in vitro model [87,88]. Zuo et al [87] designed a multiple microelectrode array, with 105 electrodes, to stimulate and record the extracellular neural signals of mouse brain slices.…”
Section: Neurodegenerative Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…From the same laboratory group, Ahnood et al describe a system with upscaled information density for retinal implants (Ahnood et al, 2017), as well as another method of generating charge in diamond electrodes through near‐infrared light (Chambers et al, 2020). Improved methods of micro‐ and nano fabrication enabled the formation of a 3D nanostructured array by Stamp et al, subsequently used for electrophysiological tests for subretinal stimulation in explanted animal retinas and found capable of localized stimulation of retinal ganglion cells (Stamp et al, 2020). Overall, CVD fabricated diamond has shown great promise as a material for electrodes, sensors and bionic interfaces, with multimodality an emerging prospect of interest from this versatile material.…”
Section: Fabrication and Application Of Different Diamond Surfaces Fomentioning
confidence: 99%